Sampling refugee groups: The example of Syrians in Turkey - David Schiefer; Franck Düvell; Ali Zafer Sağıroğlu; Lena Mann (International Migration, 2023)
Quantitative surveys among refugees not only advance our scientific understanding of forced migration, but they also provide political and civil society actors with the information they need to take measures to improve their protection and living conditions. These actors often need to acquire such information within a short period of time. However, the methods to access and survey this group to gain valid findings are subject to scientific debates. Based on a survey among Syrian refugees in Turkey, this article demonstrates a study design that generated valid knowledge about this population within a limited amount of time and resources. As a unique feature of the article, we compare our sample with four other sources of information to scrutinize how well it resembles the target population. As we can show, although point estimations differ to some extent, the internal distributions of sample characteristics are comparable across sources confirming the success of our sampling method.
Keywords: 300; access; hard-to-survey populations; methodology; refugee surveys; sampling; Turkey